2023
DOI: 10.1096/fj.202300819rr
|View full text |Cite
|
Sign up to set email alerts
|

Grape seed proanthocyanidin improves intestinal inflammation in canine through regulating gut microbiota and bile acid compositions

Mingrui Zhang,
Ruixia Mo,
Haotian Wang
et al.

Abstract: Although certain progress has been made in treating canine inflammatory bowel disease (IBD), a large proportion of dogs have a poor prognosis and may develop resistance and side effects. Therefore, it is of great significance to prevent or alleviate canine IBD through nutritional intervention. Plant polyphenol can interact with intestinal bacteria and has important prospects in the intestinal health improvement. This study evaluated the effect of grape seed proanthocyanidin (GSP), a plant‐derived natural polyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 63 publications
(144 reference statements)
0
5
0
Order By: Relevance
“…Similarly, we observed that specific gut microbiota from phyla Firmicutes act as protective factors against hypertrophic scarring, including Intestinimonas , Ruminococcus2 , Dorea , and Ruminococcus torques . Regarding the modified species, Ruminococcus torques was reported to be associated with the alleviation of inflammation through regulating bile acid compositions ( Zhang M et al, 2023 ). At the genus level, both Intestinimonas and Ruminococcus2 are butyric acid-producing bacteria, deemed potential probiotics for alleviating and treating inflammatory diseases due to their capacity to regulate T regulatory cells and inhibit Histone Deacetylase (HDAC) ( Gao et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we observed that specific gut microbiota from phyla Firmicutes act as protective factors against hypertrophic scarring, including Intestinimonas , Ruminococcus2 , Dorea , and Ruminococcus torques . Regarding the modified species, Ruminococcus torques was reported to be associated with the alleviation of inflammation through regulating bile acid compositions ( Zhang M et al, 2023 ). At the genus level, both Intestinimonas and Ruminococcus2 are butyric acid-producing bacteria, deemed potential probiotics for alleviating and treating inflammatory diseases due to their capacity to regulate T regulatory cells and inhibit Histone Deacetylase (HDAC) ( Gao et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, GS can partially restore dysbiosis produced by obesity and inflammatory bowel disease. Studies have shown a correlation between microbiota modulation and beneficial health effects [ 74 , 76 ]. Moreover, many studies of animal models have highlighted an increase in biodiversity indices after a GS-supplemented diet [ 15 , 65 , 68 , 72 ].…”
Section: Effects Of Polyphenol-rich Winemaking By-products On Gut Mic...mentioning
confidence: 99%
“…but did not improve GM diversity in fat-diet-fed rodents [ 74 ]. The work of Zheng et al, 2023, on the canine model suggested that the anti-inflammatory effect of proanthocyanidin-rich GS extract is related to GM modulation and microbiota-derived bile acids [ 76 ]. Fecal microbiota was transferred to dogs with mild inflammatory bowel disease to validate that GS extract has a beneficial ingredient with the potential to improve intestinal inflammation [ 76 ].…”
Section: Effects Of Polyphenol-rich Winemaking By-products On Gut Mic...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, antibiotic abuse is not uncommon, especially when seeking to treat bacterial infections [ 2 ]. Such abuse can trigger bacterial antibiotic resistance, and excessive dosages can disrupt the intestinal floral balance, rendering pets prone to constipation, diarrhea, and other gastrointestinal diseases that seriously endanger their health [ 3 ]. Therefore, when seeking to prevent and treat cat diseases, agents other than antibiotics are required.…”
Section: Introductionmentioning
confidence: 99%